High-power laser-plasma interaction in nanosecond regimes 'at a glance' using proton deflectometry. (May 2016) - Loiseau, P; Castan, A; Marquès, J-R; Lancia, L; Gangolf, T; Fuchs, J; Masson-Laborde, P-E; Teychenné, D; Debayle, A; Monteil, M-C; Casanova, M; Rousseaux, C; et al.
Abstract: Recent experiments indicate that controlling the propagation of high-power laser beams through millimeter long and low-density plasmas still remains challenging. In such plasma conditions, it is equally important to consider the impact of the plasma on laser propagation and laser properties, and the impact of the laser on plasma conditions. These complex phenomena are still difficult to implement in fluid models owing to the highly non-linear physics at play. Yet, electromagnetic fields prove to be good signatures of most of these low frequency phenomena. In particular, local pressure gradients and electron transport can be inferred from the electric fields. Such in-depth plasma characterization can be achieved through proton deflectometry. For that purpose, we have developed a three-dimensional simulation capability in order to compute protons' trajectories modified by the local electric fields.